Toad Poisoning: Clinical Characteristics and Outcomes - Trakulsrichai S; Chumvanichaya K; Sriapha C; Tongpoo A; Wananukul W (Dove Medical Press, 2020)
Satariya Trakulsrichai,1,2 Kritsada Chumvanichaya,1,3 Charuwan Sriapha,2 Achara Tongpoo,2 Winai Wananukul2,4 1Department of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 10400, Thailand; 2Ramathibodi Poison Center, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 10400, Thailand; 3Emergency Department, Somdech Phra Pinklao Hospital, Bangkok 10600, Thailand; 4Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 10400, ThailandCorrespondence: Satariya TrakulsrichaiDepartment of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 10400, ThailandTel +66-2-2011484Fax +66-2-2012404Email Satariya.tra@mahidol.ac.thObjective: This study was performed to describe the clinical characteristics and outcomes of patients with toad poisoning in Thailand.Methods: We carried out a retrospective study of patients with toad poisoning from the Ramathibodi Poison Center Toxic Exposure Surveillance System during a 5-year period (2012– 2016).Results: We studied 36 patients poisoned by toad toxin. The median age was 31 years. Most patients were male (66.7%) and had ingested toad meat (50%). The most common presentation was gastrointestinal (GI) symptoms with a median onset of 2 h after ingestion. Twelve patients presented with bradycardia; seven presented with shock and one with cardiac arrest. In the initial EKGs of all patients, the most common abnormality was sinus bradycardia.Two patients developed cardiac arrest early during management in the emergency room (within 15 minutes after ER arrival or within 4.5 h after ingestion). During admission, one patient developed sinus bradycardia, and two developed bradyarrhythmia; however, all three were stable. No tachyarrhythmias such as ventricular tachycardia were detected in any patient. Some patients (11.1%) presented with hyperkalemia. Serum digoxin was detected in five of seven patients tested, ranging from 0.43 to > 8 ng/mL. Most patients (75%) were admitted to the hospital; the median duration of hospitalization was 2 d (range 0.5– 5 d). The overall mortality rate was 8.3%, and all three patients that died ate toad meat and/or eggs and developed cardiac arrest. All patients received supportive with/without symptomatic care including GI decontamination, inotropic drugs, cardiac pacing, and management of hyperkalemia. One patient received intravenous calcium for hyperkalemia but did not develop dysrhythmia after calcium administration. One patient received digoxin-specific antibody fragments (DsFab), after which he clinically improved and was discharged.Conclusion: Toad poisoning commonly caused GI symptoms and bradycardia. However, in severe cases, death occurred. Tachyarrhythmia was not observed. Supportive, symptomatic care might be the main therapies for this poisoning, especially if DsFab is not available.Keywords: toads, bufotoxin, bufadienolide, cardioactive steroids, cardiac glycosides, digoxin-specific antibody fragments